2015
DOI: 10.1007/s11431-015-5887-z
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the semi-circular bend dynamic fracture toughness test using discrete element models

Abstract: The semi-circular bend (SCB) dynamic fracture toughness test is simulated using discrete element models. The influence of the frictional boundary condition, constitutive law and specimen thickness on the test measurements is investigated. It is found that friction between loading plates and the rock specimen affects the test results. Therefore, friction must be carefully considered to obtain accurate measurements. The simulation results also show that in contrast to the 2D model in which a rate-dependent cohes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…On the other hand, DEM works quite well in the dynamic rock fragmentation and fracture because of the discontinuum assumption. The examples of using this method can be found, for example, in refs [16,19,44]. Combining FEM and DEM provides a unique opportunity to have the features of continuum and discontinuum techniques in one code.…”
mentioning
confidence: 99%
“…On the other hand, DEM works quite well in the dynamic rock fragmentation and fracture because of the discontinuum assumption. The examples of using this method can be found, for example, in refs [16,19,44]. Combining FEM and DEM provides a unique opportunity to have the features of continuum and discontinuum techniques in one code.…”
mentioning
confidence: 99%
“…However, to simulate discontinuous behavior and large displacement of rock, it is more promising to use discontinuum-based methods. These methods, including particle flow code (PFC) (Li et al 2014;Li et al 2018;Xu et al 2016), universal distinct element code (UDEC) (Yan et al 2012), and distinct lattice spring model (DLSM) (Zhao et al 2014;Zhao et al 2015), have been widely used for the simulation of rock dynamics. In the realm of investigating the dynamic mechanical characteristics of rock, hybrid continuum-discontinuum approaches have gained prominence.…”
Section: Introductionmentioning
confidence: 99%
“…However, Zhao et al (2014) found that the heterogeneity or microstructure of rock only contributes limited influence to the rate dependency. To reproduce the whole rate dependency, one possible solution is to implement a rate-dependent constitutive model that establishes the relationship between loading rates and the strength parameters, which has already been used in UDEC (Zhao et al 2015), DLSM (Kazerani et al 2010) and other methods (Zhang et al 2022). However, there is insufficient research to directly validate this method with SHPB experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of theoretical and numerical research, Lim et al [17] proposed the calculation method of stress intensity factor (SIF) for notched SCB specimens in 1993, which provided a means for the study of fracture parameters in mixed mode. Zhao et al [18] used the discrete element model to numerically simulate the dynamic fracture toughness of the SCB specimen with bottom groove. Eftekhari et al [19] discussed the fracture properties of notched SCB specimens under mixed mode loading using the extended finite element method.…”
Section: Introductionmentioning
confidence: 99%